Hubungan Tingkat Pengetahuan dan Dukungan Keluarga Dengan Kemampuan Merawat Keluarga Hipertensi di RT 003/RW 006 Tugu Cimanggis Kota Depok Tahun 2023 - Umi Salamah; Lannasari Lannasari; Sancka Stella (STIKES Columbia Asia Medan, 2024)
Hypertension is a very serious problem and must be watched out for because this disease is one of the diseases that causes death. Lack of level of knowledge and family support as well as the ability to care for the family will influence care that is not optimal. Family is one of the environmental factors that influences the development of disease. Therefore, the family plays an important role in maintaining and caring for family members who suffer from hypertension. Knowing that there is a relationship between the level of knowledge and family support and the ability to care for families with hypertension at Rt 003/Rw 006 Tugu Cimanggis, Depok City. This research uses a descriptive correlation research design with a cross-sectional research design. The population of this study was 42 respondents at Rt 003/Rw 006 Tugu Cimanggis, Depok City. The sampling technique used total sampling with a total of 42 respondents. The Spaerman Rank correlation test obtained strong significant values, namely P-Value 0.027 and 0.026 (< 0.05), which means there is a relationship between the level of knowledge and family support and the ability to care for families with hypertension at Rt 003/Rw 006 Tugu Cimanggis, Depok City. There is a relationship between the level of knowledge and family support and the ability to care for families with hypertension at Rt 003/Rw 006 Tugu Cimanggis, Depok City 2023.